MAKE IN INDIA: IMPACT ON MACRO ECONOMIC INDICATORS OF INDIAN ECONOMY (International Journal of Food and Nutritional Sciences, 2022)
India is one of the fastest-growing economies in the world. India needs to concentrate more on strategies that increase investment and emphasizes manufacturing, thereby opening the economy globally. 'Make in India' is a movement launched by the Government of India to encourage companies around the world to invest and manufacture their products in India. The present paper analyses the effect of the 'Make in India' initiative on various macroeconomic indicators of the Indian economy. The study also reviews the victory of the 'Make in India' strategy in its initial period. The study is solely based on secondary sources of data. In order to support the findings of the literature assembled, mathematical and appropriate statistical tools have been applied. Results of the paper show that the effect of the 'Make in India' campaign in building best-class manufacturing infrastructure, facilitating investment, and protecting intellectual property is increasing.